Th17/Treg immunoregulation and implications in treatment of sulfur mustard gas-induced lung diseases. (2nd December 2017) - Iman, Maryam; Rezaei, Ramazan; Azimzadeh Jamalkandi, Sadegh; Shariati, Parvin; Kheradmand, Farrah; Salimian, Jafar
ABSTRACT: Introduction : Sulfur mustard (SM) is an extremely toxic gas used in chemical warfare to cause massive lung injury and death. Victims exposed to SM gas acutely present with inhalational lung injury, but among those who survive, some develop obstructive airway diseases referred to as SM-lung syndrome. Pathophysiologically, SM-lung shares many characteristics with smoking-induced chronic obstructive pulmonary disease (COPD), including airway remodeling, goblet cell metaplasia, and obstructive ventilation defect. Some of the hallmarks of COPD pathogenesis, which include dysregulated lung inflammation, neutrophilia, recruitment of interleukin 17A (IL −17A) expressing CD4 + T cells (Th17), and the paucity of lung regulatory T cells (Tregs), have also been described in SM-lung. Areas covered : A literature search was performed using the MEDLINE, EMBASE, and Web of Science databases inclusive of all literature prior to and including May 2017. Expert commentary : Here we review some of the recent findings that suggest a role for Th17 cell-mediated inflammatory changes associated with pulmonary complications in SM-lung and suggest new therapeutic approaches that could potentially alter disease progression with immune modulating biologics that can restore the lung Th17/Treg balance.